2019
DOI: 10.1002/aic.16778
|View full text |Cite
|
Sign up to set email alerts
|

Classification and identification of gas–liquid dispersion states in a jet bubbling reactor

Abstract: Three gas-liquid dispersion states including flooding, loading, and complete dispersion are observed sequentially in a jet bubbling reactor with an increase of the liquid jet velocity at the nozzle outlet (u j). The gas-liquid dispersion states are identified through the slope (k) of the curve of fluctuation distribution index (FI) versus u j as follows: (a) under the flooding, k = 0; (b) under the loading, k > 0; (c) under the complete dispersion, k < 0. In particular, the u j at the transition points from fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Under the conditions of stirring and bubbling in the experiment, four annular tube air volumes (10, 20, 30, and 40 L/min) and five stirring speeds (50, 100, 150, 200, and 250 rpm) are set to obtain different flow numbers Fl and Froude numbers Fr . The bubbly flow regimes under different working conditions are observed and recorded 10,19,39,40 . The bubbly flow regime distribution diagram and transition curve in this experiment are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 93%
“…Under the conditions of stirring and bubbling in the experiment, four annular tube air volumes (10, 20, 30, and 40 L/min) and five stirring speeds (50, 100, 150, 200, and 250 rpm) are set to obtain different flow numbers Fl and Froude numbers Fr . The bubbly flow regimes under different working conditions are observed and recorded 10,19,39,40 . The bubbly flow regime distribution diagram and transition curve in this experiment are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 93%
“…The results of our previous studies have shown that bubbles are broken up very sharply near the exit of the liquid jet, and a large number of microbubbles are generated. , In addition, we also found that the liquid jet can not only break up the bubbles but also plays an important role in dispersing the bubbles. When the vertically downward liquid jet contacts the rising bubbles in the countercurrent, the bubbles are dispersed to the surrounding area, and the bubble radial dispersion width increases with the liquid jet velocity increasing. , Based on the flow field characteristics of the liquid jet stated above, we can speculate that it is an effective and feasible method to generate and disperse microbubbles through the impingement of the liquid jet on the gas.…”
Section: Introductionmentioning
confidence: 96%
“…When the vertically downward liquid jet contacts the rising bubbles in the countercurrent, the bubbles are dispersed to the surrounding area, and the bubble radial dispersion width increases with the liquid jet velocity increasing. 29,30 Based on the flow field characteristics of the liquid jet stated above, we can speculate that it is an effective and feasible method to generate and disperse microbubbles through the impingement of the liquid jet on the gas. There are many reports in the literature on the jet-impinging gas sparger for bubble production.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Compared with the gas-liquid stirred tank, it has the advantages of low energy consumption and simple operation. Some works about the jet bubbling reactor have been done by researchers, [1][2][3][4][5][6][7][8] whose studies are mainly concentrated on the liquid macromixing, [1][2][3] gas-liquid flow patterns, 4,5 mass transfer, 3,6 and bubble swarm motion. 7,8 However, the prediction of bubble size distribution, which is very important for determining interfacial areas and mass transfer rates when designing and scaling up the jet bubbling reactor, is still a difficult issue.…”
Section: Introductionmentioning
confidence: 99%